Tourism Planning Challenges and Prospects in A Destination with Political Conflict: The Case Study of Nablus City, Palestine - Jumah, Balsam (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
The phenomenon of tourism is a direct pathway to economic growth and international peace. It is a highly political-sensitive sector to such as wars, protesting, partisan conflicts, crises and terrorism, which will result in a distorted image of the destination leading to an alienation of tourists. The state of Palestine particularly Nablus city suffered from the volatility of the tourist situation due to the ‘Zionist Occupation’ who considers Nablus as ‘The City of Terrorism’, as it has a unique geographical location and high potentials, which led to the creation of challenges and pressures on the city and its people. This study aims to shed the light on the political challenges that beset tourism development and its adequate planning. This research is also tries to provide an overview of Nablus city including the demographic characteristics, explaining its touristic status and exploring the city’s potentials. This study is also exploring the constraints facing the Palestinian tourism in Nablus city. For the purpose of this study, a qualitative/inductive method was employed. Data collection and analysis involved an in-depth interview with various respondents who are associated with the tourism related institutions. Overall, 20 respondents were located and interviewed. The study revealed that lack of adequate infrastructure is curtailing the development of tourism. The study also explored that the occupation is one of the major hindrance to the establishment and consolidation of a productive tourism sector. Another important finding of the research is lack of trained human resources and inadequate services, especially in accommodation sector. A novel solution is also suggested that could become a pathway to revive the tourism sector in Nablus. The implications and limitations of the study is also discussed. Keywords: Tourism planning, Political conflict, Occupation, Palestine, Nablus

ÖZ: Turizm olgusu, doğrudan ekonomik büyümeye ve uluslarası barışa giden yoldur. Bu sektör, savaşlara, protestolara, partizan çatışmalarına, krizlere ve terörizme siyasi olarak hassas olduğu için gidilen destinasyonun imajını bozar, bu da turistlerin bu destinasyondan uzaklaşmasına sebep olur. Filistin devleti ve özellikle Nablus şehri turist durumundaki süreksizlikten dolayı zarar görmüştür. Bunun sebebi "Siyonist İşgali"’nin Nablus’u "Terörizm Şehri" olarak saymasındandır. Nablus şehrinin benzersiz coğrafi konumu ve yüksek potansiyelinden dolayı Siyonist İşgali’nin bu şehir ve insanlarını baskılayıp zorluk çıkarmasına sebep olmuştur. Bu çalışmanın amacı, turizm gelişiminin ve bu turizm gelişiminin uygun planlamasını saran siyasi zorluklar hakkında konuyu aydınlatmaktır. Bu araştırma aynı zamanda Nablus şehri’nin demografik karakteristikleri, şehrin turistik durumunu açıklayan ve şehrin potansiyeli hakkında genel bilgi vermektedir. Ayrıca, Nablus şehrindeki Filistin turizminin karşılaştığı kısıtlama ve baskıları da incelemektedir. Araştırmanın amacından dolayı niteliksel/tümevarım metodu seçilmiştir. Veri toplanması ve analizi için turizm sektörü ile alakalı kurumlardan çeşitli katılımcılarla derinlemesine görüşme olarak mülakat yapılmıştır. Toplam olarak 20 katılımcı tespit edilip, mülakat yapılmıştır. Bu çalışma, yetersiz altyapının olması turizmin gelişmesine engel olduğunu ortaya çıkramıştır. Aynı zamanda, bu çalışma bahsedilen işgalin, üreten turizm sektörünün tesis edilmesinde ve kuvvetlendirilmesindeki en büyük engellerden biridir. Bu araştırmanın bir başka önemli bulgusu da, özellikle konaklama sektöründe yetiştirilmiş insan kaynaklarının eksikliği ve yetersiz hizmetin oluşudur. Araştırmada, Nablus’taki turizm sektörünün canlanmasında yenilikli bir çözüm yolu olabilecek bir çözüm önerilmiştir. Çalışmanın çıkarımlarına ve sınırlamalarına da yer verilmiştir. Anahtar kelimeler: Turizm planlaması, Siyasi çatışma, Işgal, Filistin, Nablus
Master of Science in Tourism Management. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Tourism, 2019. Supervisor: Prof. Dr. Habib Alipour.
Keywords: Tourism; Tourism--Nablus City (Palestine); Tourism planning; Political conflict; Occupation; Palestine; Nablus